Microbiological quality analysis of domestic water collected from the slum area’s people in Dhaka city - Nur, Ifra Tun; Baishnab, Rakhi; Tethee, Niger Sultana (Stamford Journal of Microbiology, 2017)
Over the last few consecutive decades along with urbanization slum population has been raised. But unfortunately unsatisfactory water supply and sanitation systems are the main obstacles of their livelihood and they are suffering from many diseases. So our present study attempted to focus on the existence of pathogenic microorganisms in domestic water used by slum population along with drug resistant pattern of the isolated bacteria. Total 20 samples were collected and processed for microbiological action. Significant numbers of coliform bacteria especially Escherichia coli and Klebsiella spp. were found within the range of 102 to 104 cfu/ml. Conversely almost all samples exhibited fecal contamination except sample 5 and 6. Growth of fungus and other pathogenic bacteria such as Staphylococcus spp. and Vibrio spp. also found in almost every sample. Total 10 available drugs were used against the identified isolates. Most of the identified bacteria were found to be sensitive against commonly used antibiotics. Resistance was found only against ampicilin, amoxycilin and vancomycin. Stamford Journal of Microbiology, Vol.7(1) 2017: 19-22